Analisis Pengaruh Tekanan Mesin Exsstruder Terhadap Kuat Tekan Hasil Produk Bata Merah - Irwan Suriaman; Sendi Ariyandi; Wawan Wawan; Ariyandi Ariyandi; Uus Supriatna (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
This research was conducted to analyze the performance of the extruder machine on the production quantity and quality of bricks. Analysis shows that the engine transmission uses a type B belt with a belt circumference of 1063.622 mm, so the v belt used by the motorbike has a nominal belt number of 41 inches. From the results of the linear regression of red bricks before being burned with a correlation value of 98.7%, it can be categorized as very strong. The linear regression for red bricks before burning is 0.10 while alpha < 0.05 so it can be concluded that there is no significant influence on variables X and Y. The linear regression for red bricks after burning is 0.07 while alpha < 0.05 so It can be concluded that there is no significant influence on variables X and Y.